Learning Environment and Attitudes Associated with an Innovative Science Course Designed for Prospective Elementary Teachers - Martin-Dunlop, Catherine; Fraser, Barry (Springer, 2008)
This study assessed the effectiveness of an innovative science course for improving prospective elementary teachers’ perceptions of laboratory learning environments and attitudes towards science. The sample consisted of 27 classes with 525 female students in a large urban university. Changing students’ ideas about science laboratory teaching and learning and creating more positive attitudes towards science were accomplished by using a guided open-ended approach to investigations, together with instructors who used cooperative learning groups to create a supportive environment. Ideas and attitudes prior to the course were assessed using a questionnaire focusing on the students’ previous science laboratory courses, and these were compared to data collected at the end of the course. Students reported large and statistically significant improvements on all seven scales assessing the laboratory learning environment and attitudes towards science. The largest gains were observed for Open-Endedness and Material Environment (with effect sizes of 6.74 and 3.82 standard deviations, respectively). An investigation of attitude-environment associations revealed numerous positive and statistically significant associations in both univariate and multivariate analyses. In particular, the level of Instructor Support was the strongest independent predictor of student attitudes at two levels of analysis.